2017
DOI: 10.1016/j.jadohealth.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Prescription Stimulant Use Among Girls 10–18 Years of Age: Associations With Other Risky Behavior

Abstract: Purpose Little is known about the risk factors for nonmedical use (NMU) of prescription stimulants among adolescent girls. We aimed to measure the association of nonmedical prescription stimulant use with empirically linked risk factors, including weight control behavior (WCB), gambling, and depressed mood, in pre-teen and teenaged girls. Methods We assessed the relationship between age and race, gambling, WCB, depressive mood, and nonmedical prescription stimulant use using multivariable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Ultimately, this discrepancy is likely to result from methodological differences; while the previous work only assessed last source used, this work included all past-month sources. The link between specific PDM sources and MDD in this study is consistent with the clustering of PDM, across medication classes, and MDD in adolescents 7,[34][35][36][37] and highlights the need for comprehensive mental health evaluations of and intervention in at-risk youth. Links between past-year anxiety diagnosis or mental health treatment and PDM were much more inconsistent, suggesting a general lack of an association.…”
Section: Discussionsupporting
confidence: 78%
“…Ultimately, this discrepancy is likely to result from methodological differences; while the previous work only assessed last source used, this work included all past-month sources. The link between specific PDM sources and MDD in this study is consistent with the clustering of PDM, across medication classes, and MDD in adolescents 7,[34][35][36][37] and highlights the need for comprehensive mental health evaluations of and intervention in at-risk youth. Links between past-year anxiety diagnosis or mental health treatment and PDM were much more inconsistent, suggesting a general lack of an association.…”
Section: Discussionsupporting
confidence: 78%
“…82 More recent nationally representative adolescent data indicated that 18.1% of adolescents used multiple sources. 136 The greatest difference between the older (which did not include multiple sources) and newer data was in use of friends or family to obtain stimulant medication for free (29.0% versus 47.2%), 41 suggesting that adolescents obtaining stimulant medication from friends or family for free may have high rates of multiple source use.…”
Section: Medication Sources For Prescription Stimulant Misusementioning
confidence: 99%
“…There is a clear female peak at 18 years and a bimodal distribution in males with peaks at 17 and 20 years, per NSDUH data in those 12 to 21 years of age. 135 Other research in adolescents 10 to 18 years points toward increasing prevalence across this age window, 136,137 corresponding with increases in receipt of diverted stimulant medication. 138 Young adults have the highest stimulant PDM point prevalence rates, 36,37,52 with evidence that current full-time college students and recent college graduates have the highest rates within young adults.…”
Section: Prescription Stimulant Misuse Across the Lifespan Prevalencementioning
confidence: 99%
“…methylphenidate or Ritalin) or narcolepsy (e.g. modafinil), with consistently high rates reported among college students who report using the drugs to enhance academic performance (a 2015 meta-analysis estimated the prevalence to be 17% – Benson, Flory, Humphreys, & Lee, 2015) and recent evidence indicating use amongst school-age adolescents (Benson et al, 2015; Han, Jones, Blanco, & Compton, 2017; Striley, Kelso-Chichetto, & Cottler, 2017; Wang, Cottler, & Striley, 2015). There is a relative dearth of information about the nonmedical use of antipsychotic or antidepressant medications, classes which have little by way of immediately rewarding or stimulating properties, and for which nonmedical use is therefore likely to represent self-medication (although with some exceptions (Chiappini & Schifano, 2018)).…”
Section: Introductionmentioning
confidence: 99%